2014
DOI: 10.1080/00071668.2014.925090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat stress onGHR,IGF-I,ANT,UCPandCOXIIImRNA expression in the liver and muscle of high and low feed efficiency female quail

Abstract: 1. A study was conducted to test the hypothesis that feed efficiency (FE) correlated with the expression of genes from the somatotropic axis and mitochondrial genes involved in energy production, and that the environment to which the birds are exposed influenced the expression of such genes. 2. Quails were divided into High-FE and low-FE groups and maintained in a comfortable or heat stress (HS) (38°C for 24 h) environment to evaluate changes in insulin-like growth factor I (IGF-I), growth hormone receptor (GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…According to the results shown in Fig 1, the expression of ANT gene in the breast muscle of laying hen was significantly higher in the low-CP + AA group when compared with other groups (P<0.01), while it did not differ significantly between high-CP and low-CP groups. Botteje and Carstens (2009) found that AA supplementation to low protein diets improved the FE in broilers, which has also been reported in quails (Gasparino et al (2014). Our study has also shown that amino acid supplementation resulted in a better growth performance of laying hens, affected the expression of the ANT gene and altered the peak FE.…”
Section: Resultssupporting
confidence: 85%
“…According to the results shown in Fig 1, the expression of ANT gene in the breast muscle of laying hen was significantly higher in the low-CP + AA group when compared with other groups (P<0.01), while it did not differ significantly between high-CP and low-CP groups. Botteje and Carstens (2009) found that AA supplementation to low protein diets improved the FE in broilers, which has also been reported in quails (Gasparino et al (2014). Our study has also shown that amino acid supplementation resulted in a better growth performance of laying hens, affected the expression of the ANT gene and altered the peak FE.…”
Section: Resultssupporting
confidence: 85%
“…GHR mRNA abundance in hepatic tissue of lactating Holstein dairy cows (Deane and Woo, 2005;Rhoads et al, 2010) and avian species (Gasparino et al, 2014;Del Vesco et al, 2015), and is independent of the heat-induced feed intake reduction (Collier et al, 2008). Additionally, although not always observed (Rhoads et al, 2009), circulating GH levels decline in HS compared to TN cattle (Farooq et al, 2010); this decrease in circulating GH is attributed to reduced GH secretion at the pituitary gland.…”
Section: Resultsmentioning
confidence: 99%
“…The IGF-1 is an endocrine, autocrine and paracrine growth factor that plays a major role in the cell growth, development and differentiation (Delafontaine, Song, & Li, 2004). Significantly reduced PBMC IGF-1 mRNA expression in OHS group could be attributed to the reduction in protein synthesis and higher level of protein breakdown in these animals (Gasparino et al, 2014). Lower rates of IGF-1 mRNA expression in OHS animals indicate the compromised growth performance in Osmanabadi breed.…”
Section: Discussionmentioning
confidence: 99%